Saving Private Hypertext: Requirements and Pragmatic Dimensions for Preservation - Marshall, Cathy; Golovchinsky, Gene (HYPERTEXT '04: Proceedings of the fifteenth ACM conference on Hypertext and hypermedia, 2004)
The preservation of literary hypertexts presents significant challenges if we are to ensure continued access to them as the underlying technology changes. Not only does such an effort involve standard digital preservation problems of representing and refreshing metadata, any constituent media types, and structure; hypertext preservation poses additional dimensions that arise from the work’s on-screen appearance, its interactive behavior, and the ways a reader’s interaction with the work is recorded. In this paper, we describe aspects of preservation introduced by literary hypertexts such as the need to reproduce their modes of interactivity and their means of capturing and using records of reading. We then suggest strategies for addressing the pragmatic dimensions of hypertext preservation and discuss their status within existing digital preservation schemes. Finally, we examine the possible roles various stakeholders within and outside of the hypertext community might assume, including several social and legal issues that stem from preservation.